Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Bermuatan Pendidikan Karakter Pada Materi Sistem Ekskresi Kelas XI SMA - Siti Khodizah; Lufri Helendra; Relsas Yogica (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2022)
The purpose of this study was to determine the level of validity and practicality of the LKPD containing character education in the excretory system material for class XI SMA. This type of research is development research using the ADDIE development model which consists of 5 stages of activities, namely analysis, design, develop, implementation, and evaluation.The subjects of this study were 2 lecturers and a biology teacher as validators, as well as 17 students of class XII science at SMAN 11 Sijunjung. The instrument used in this study was a product validity and practicality sheet. The data obtained from the results of validity and practicality were analyzed by descriptive statistics. The validity results show a value of 96.85% with very valid criteria and a practicality value of 87.40% with very practical criteria. So, it can be concluded that the LKPD containing character education in the excretory system material for class XI SMA is valid and practical.